A Global Longitudinal Study Examining Social Restrictions Severity on Loneliness, Social Anxiety, and Depression - Lim, Michelle H.; Qualter, Pamela; Thurston, Lily; Eres, Robert; Hennessey, Alexandra; Holt-Lunstad, Julianne; Lambert, Gavin W. (Frontiers in Psychiatry, 2022)
Purpose: Social restrictions and government-mandated lockdowns implemented worldwide to curb the SARS-CoV-2 virus disrupted our social interactions, behaviours, and routines. While many studies have examined how the pandemic influenced loneliness and poor mental health, such as depression, almost none have focused on social anxiety. Further, how the change in social restrictions affected change in mental-health and well-being has not yet been explored. Methods: This is a longitudinal cohort study in community dwellers who were surveyed across three timepoints in the first six months of the pandemic. We measured loneliness, social anxiety, depression, and social restrictions severity that were objectively coded in a sample from Australia, United States, and United Kingdom (n = 1562) at each time point. Longitudinal data were analysed using a multivariate latent growth curve model. Results: Loneliness reduced, depression marginally reduced, and social anxiety symptoms increased as social restrictions eased. Specific demographic factors (e.g., younger age, unemployment, lower wealth, and living alone) all influenced loneliness, depression, and social anxiety at baseline. No demographic factors influenced changes for loneliness; we found that those aged over 25 years reduced faster on depression, while those younger than 25 years and unemployed increased faster on social anxiety over time. Conclusions: We found evidence that easing social restrictions brought about additional burden to people who experienced higher social anxiety symptoms. As country-mandated lockdown and social restrictions eased, people are more likely report higher social anxiety as they readjust into their social environment. Mental health practitioners are likely to see higher levels of social anxiety in vulnerable communities even as social restrictions ease.